2011
DOI: 10.1016/j.socec.2010.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Different effects of social capital on health status among residents: Evidence from modern Japan

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 24 publications
1
2
0
1
Order By: Relevance
“…The final model explains about 14%, 5%, 10%, and 6% of variation in SRH in China, Japan, Korea, and Taiwan, respectively. These are similar to the SRH variations explained by prior studies conducted in East Asia (Cai et al, 2017; Oshio et al, 2011; Yamamura, 2011). The full model does not suffer from multicollinearity because the variance inflation factor (VIF) score is lower than 2 (Lin, 2008).…”
Section: Resultssupporting
confidence: 88%
“…The final model explains about 14%, 5%, 10%, and 6% of variation in SRH in China, Japan, Korea, and Taiwan, respectively. These are similar to the SRH variations explained by prior studies conducted in East Asia (Cai et al, 2017; Oshio et al, 2011; Yamamura, 2011). The full model does not suffer from multicollinearity because the variance inflation factor (VIF) score is lower than 2 (Lin, 2008).…”
Section: Resultssupporting
confidence: 88%
“…In this scenario, the digital divide is likely to become an important factor in social exclusion, which may exacerbate inequalities in well-being as well as capabilities. The literature has shown that social interactions and the accumulation of social capital positively influence subjective well-being (Becchetti et al, 2008;Bruni & Stanca, 2008), health (D'Hombres et al, 2010;Yamamura, 2011a), education (Yamamura, 2011b;Misra et al, 2013), employability (Fugate et al, 2004;McDonald, 2011), economic welfare and social mobility (Degli Antoni, 2009;Yamamura, 2012), entrepreneurship (Alexy et al, 2012;Santarelli & Tran, 2013), access to credit (Shoij et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Selain itu, menikah juga mampu mengurangi stress karena terdapat rasa cinta dan berbagi dengan pasangan serta dengan menikah mampu membuat pasangan lebih memperhatikan kondisi kesehatan satu sama lain sehingga bisa mengurangi kecenderungan gaya hidup yang buruk. Hal ini berbeda dengan orang yang bercerai, dimana menurut Pandey (2008) dan Yamamura (2009) perceraian akan memberikan dampak yang buruk terhadap kesehatan seperti depresi serta peningkatan dalam hal konsumsi obat-obatan.…”
Section: Status Perkawinanunclassified